Trends in Research on PBL-Based E-Worksheets to Enhance Students' Critical Thinking Skills: A Systematic Literature Review (2016–2025) - Nihla Utami; Gito Hadiprayitno; Imam Bachtiar (Balai Publikasi Indonesia, 2026)
Critical thinking skills are essential competencies that students must possess in order to apply knowledge and skills acquired through learning to everyday situations and to face the challenges of an ever-evolving era. These skills can be facilitated through learning using the Problem-Based Learning (PBL) model. This study aims to identify and analyze research trends on PBL-based electronic student worksheets (E-LKPD) for enhancing students’ critical thinking skills. The research employs a descriptive and analytical method. The data were obtained from documents indexed in Google Scholar from 2016 to 2025, using the tools Publish or Perish and Dimension.ai. The research procedure follows the PRISMA guidelines, focusing on the types of publications, sources of publications, and the most-cited research titles related to PBL-based E-LKPD. Data analysis was conducted using bibliometric analysis with the aid of VOSviewer software. The results indicate a trend in research on PBL-based E-LKPD for improving students’ critical thinking skills from 2016 to 2025. There has been an increase in the number of publications from 2016 to 2023, although a decline was observed in 2024